Long Noncoding RNA DSCAM-AS1 Facilitates Proliferation and Migration of Hemangioma Endothelial Cells by Targeting miR-411-5p/TPD52 Axis. (11th October 2022) - Wang, Yulong; Zhai, Shuiting; Xing, Jianwu; Zhang, Jinchi; He, Yingkun; Wang, Guoquan; Li, Tianxiao
Abstract : Background . Diagnosed as a kind of vascular neoplasm of infancy, hemangioma (HA) occurs mainly due to the aberrant proliferation of endothelial cells. Existing evidence has manifested the close relationship of long noncoding RNAs (lncRNAs) with the pathogenesis of HA. Although lncRNA DSCAM antisense RNA 1 (DSCAM-AS1) has been revealed to be implicated in the progression of human diseases, the underlying mechanism DSCAM-AS1 exerts in HA formation is unclear. Aims . To figure out how DSCAM-AS1 may regulate the progression of human hemangioma endothelial cells (HemECs). Methods . DSCAM-AS1 expression was verified through RT-qPCR detection. Functional assays including EdU assay, colony formation assay, flow cytometry analysis, TUNEL assay, and transwell assay were applied to evaluate cell proliferation, apoptosis, and migration upon DSCAM-AS1 knockdown. Moreover, RNA pull-down assay, luciferase reporter assay, RIP assay, and other mechanism experiments were utilized for evaluating the correlation of DSCAM-AS1 and RNAs in HemECs. Results . DSCAM-AS1 knockdown inhibited proliferative capability and migratory capability of HemECs whereas expedited apoptosis. Molecular mechanism results testified DSCAM-AS1 could function as a ceRNA to bind miR-411-5p in HemECs. Besides, it was confirmed that tumor protein D52 (TPD52) served as a downstream target of miR-411-5p in HemECs. More importantly, related rescue assays uncovered that elevated expression of TPD52 or inhibited expression of miR-411-5p reversed the repressive progression of HemECs mediated by DSCAM-AS1 depletion. Conclusion . DSCAM-AS1 expedited HA progression via miR-411-5p/TPD52 pathway, which provided a novel therapeutic option for HA treatment.